Low Cost Technology Developed and Used for Screening and Selecting Few Field and Vegetable Crops for Tolerance to Few Abiotic Stresses - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Satya, P.; Sagar, P. V. (International Journal of Bio-resource and Stress Management, 2023)
Stress is a global threat in achieving potential crop yield. Abiotic stresses like drought, salinity, heat stress and other abiotic stresses associated several associated with ever increasing human populations affect crop productivity drastically under sustainable agriculture in the farmers fields. Though significant research activities have been taken place to address these problems with respect to the mechanism of resistance and crop improvement but little progress has been achieved. Here, several low cost technologies have been developed for screening crop cultivars for few abiotic stresses viz. screening for tolerance to salinity, drought, heat stress, flooding and cold stress. Seedling Emergence percentage, tap root length and number of lateral roots was considered important parameters for selection of salinity tolerant hybrids in cotton. Salinity tolerant genotypes showed high emergence percentage under saline concentration compared to remaining genotypes. These hybrids produced more number of profuse lateral roots and long tap roots in saline concentration compared to control for osmotic adjustment and increase in tap root length. 90% of seeding survival may be selected for heat tolerant at seedling stage. These hybrids may be recommended for growing under heat and drought stress prone areas for better adaptation. Hybrids with thick leaves, stout petiole, good survival under drought & recovery from stress are considered for selecting drought resistant hybrids in castor